The representation of Quito’s southern neighborhoods in the last mayoral election. Isotropy deficit or shortage of respect? - Alfredo Santillán (Íconos)
The last mayoral election in Quito produced a totally unexpected outcome, which contradicted all polls published before the election. Early attempts to explain the results centered on the voting patterns of the city´s southern neighborhoods, which concentrate a massive lower-income population. Further analysis by specialists has tended to reject this hypothesis and privileged other potential accounts. This article draws from the “Paradigm of Recognition”, in an effort to understand the political practices that could provide meaning to the expression “The South´s Administration” when referring to the recently inaugurated city government. Based on information on the various everyday forms of dispute over the meaning of the “The South” in Quito, this article suggests that a sense of territorial belonging constitutes the main platform for the building of political sense among the dwellers of this part of the city. This confirms what was already mentioned by several political organizations in the Southern districts of Quito as a possible explanation of the observed outcome, even prior to the election itself.